PENINGKATAN KESADARAN ANTI-BULYING MELALUI BIMBINGAN KELOMPOK TEKNIK SOSIODRAMA - Hartuti (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
This research aims to raise awareness of anti-bullying in class X MIPA1 SMAN 1 Kasihan through sociodrama techniques. This type of research is class action research with the research subjects of class X students of SMAN 1 Pity numbering 32 students. This research was carried out in 2 cycles in collaboration between researchers and fellow teachers of BK (Dra.Rr). Sri Astuti) which starts from March 16 to May 7, 2019. The implementation of sociodrama techniques is carried out in 2 cycles where in cycle I includes 3 actions in 3 meetings and cycle II includes 2 actions in 2 meetings. The methods of data collection used are psychological scale, observation and interviewing. The instruments used are anti-bullying awareness scales, observation guidelines and interview guidelines. Data analysis uses descriptive analysis. The actions taken in this study were: bullying video playback, discussion and sociodrama. Sociodrama carried out in cycle I uses a play script, while in cycle II without using a play script. In cycle I the aspect of anti-bullying consciousness appears in the sensing aspect, while in cycle II aspects of feelings, actions and thoughts. The increase in anti-bullying awareness is evidenced by the acquisition of post-test results by 55.22%, cycle I by 74.47% and cycle II by 80.34% which is in the high category. The results of this study suggest that anti-bullying awareness can be improved through sociodrama techniques.